Engagement logics: How partners for sustainability-oriented innovation manage differences between organizational logics - Watson, Rosina; Wilson, Hugh N.; Macdonald, Emma K. (Wiley, 2025)
Innovation partnerships frequently experience tensions due to differences in partners' organizational logics. The literature recommends that partners adopt collaborative, empathetic mindsets but even so, tensions can threaten outcomes and partnership continuation. Difficulties can be exacerbated when firms engage stakeholder organizations in sustainability-oriented innovation projects, where each partner is seeking their own combination of social, environmental, and economic objectives. This study explores strategic responses to these differences in logics through eight case studies of sustainability-oriented innovation engagements between a focal business and an external organization. The key finding is that partners can respond to their differing logics by shaping a new “engagement logic” that guides members of both (or all) organizations. A logic frame with four value-related dimensions—value salience, instrumentality, temporality, and language—allows a subtly idiosyncratic engagement logic to be created that is acceptable to both parties. This classification of ingredients of a logic frame forms a wider contribution to the institutional-logics literature. A complementary range of logic practices is identified, covering logic emergence, logic enactment, and boundary defining. The engagement logic aids the partnership by contributing to four partnership-level generative outcomes: partnership commitment, capability integration, scope flexibility, and system orientation. A notable finding is the presence of a logic boundary, specified in work, time, and space, enabling the engagement logic to co-exist with organizational logics; a research direction is whether this boundary also exists in logics at organizational and field levels. The study shows partnerships to be a new context within which novel logics can emerge, contributing to an understanding of how logics evolve.
Keywords: cross-sector; innovation; institutional logics; partnership; sustainability